Fermentative production of chiral acetoin by wild-type Bacillus strains. Issue 2 (7th February 2020) - Zhong, Haoxuan; Wang, Linhui; Zhao, Jing-yi; Xiao, Zijun
Abstract: In recent years, there have been many studies on producing acetoin by microbial fermentation, while only a few studies have focused on chiral acetoin biosynthesis. The weight assignment method was first applied to balance the chiral purity (expressed as the enantiomeric excess value) and the titer of acetoin. Bacillus sp. H-18W, a thermophile, was selected from seven Bacillus strains for chiral acetoin production. To lower the cost of the fermentation medium, soybean meal was used as a feedstock. Four kinds of frequently used commercial proteinases with different active sites were tested for the hydrolyzation of the soybean meal, and the combination of the acidic proteinase and the neutral proteinase showed the best results. In a fermentation medium containing 100 g L −1 glucose and 200 g L −1 hydrolysate, Bacillus sp. H-18W produced 21.84 g L −1 acetoin with an ee value of 96.25% at 60 h. This is the first report of using a thermophilic strain to produce chiral acetoin by microbial fermentation. Thermophilic fermentation can reduce the risk of bacterial contamination and can save cooling water. Using soybean meal hydrolysate and glucose as feedstocks, this work provides an economical and alternative method for the production of chiral pure acetoin.